Guest

( * ) (cot theta + cosec theta – 1 ) / (cot theta – cosec theta + 1) =

( * )
(cot theta + cosec theta – 1 ) / (cot theta – cosec theta + 1)  =

Grade:11

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
7 years ago
Hello student, Please find the answer to your question below

(cot theta + cosec theta – 1 ) / (cot theta – cosec theta + 1)
= cot 2theta - (cosec theta – 1)2
= cot 2theta - (cosec2 theta +1 – 2 cosec theta)
= cot 2theta – cosec2 theta -1 + 2 cosec theta
= -2 +2 cosec theta

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free